1969
DOI: 10.1002/bit.260110307
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and use of insolubilized amyloglucosidase for the production of sweet glucose liquors

Abstract: SummaryAmyloglucosidase (EC. 3.2.1.3), partially purified from an Aspergillus species, was chemically attached to DEAE cellulose using the bifunctional reagent 2-amino-4,6-dichloro-s-triazine. The action of the insolubilized enzyme derivative on dilute maltose and dextrin solutions was studied in a packed bed. A second and deeper bed was used to demonstrate the possibility of a continuous process for raising the dextrose equivalents of "glucose" liquors of high concentration formed by acid hydrolysis of maize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

1972
1972
1989
1989

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…Lilly and coworkers (Kayetal. 1968;Seif et al 1969;Sharp et al 1969;Wilson et al 1969) have prepared immobilised enzymes on filter paper and DEAE filter paper, the activities of which were maintained after storage for two years at 2-5°C (Lilly 1971). Broun and co-workers (Broun et al 1969(Broun et al , 1973 have studied the immobilisation of enzymes on cellophane.…”
Section: Introductionmentioning
confidence: 99%
“…Lilly and coworkers (Kayetal. 1968;Seif et al 1969;Sharp et al 1969;Wilson et al 1969) have prepared immobilised enzymes on filter paper and DEAE filter paper, the activities of which were maintained after storage for two years at 2-5°C (Lilly 1971). Broun and co-workers (Broun et al 1969(Broun et al , 1973 have studied the immobilisation of enzymes on cellophane.…”
Section: Introductionmentioning
confidence: 99%
“…Recent development of various techniques of immobilization of enzymes provides the possibility to utilize them in a cyclic or continuous process many times, thus lowering the costs and eventually simplifying the technological operations. GA was immobilized through covalent bonds to ceramic supports [ 11, porous glasses [2], DEAE-cellulose [3], bonding to neutral carriers through metal ions [S], entrapment in polyacrylamide gel [4]. A particulary suitable method for immobilizing the enzyme is its adsorption in view of an easy access of substrate and simplicity of the preparation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The sources of these enzymes and their potential applications for industrial use have been reviewed (Underkofler and Danault, 1965;Sherwood, 1966;Wurzburg and Szymanski, 1970;Allen and Dawson, 1975). Several investigators have reported preparations of insolubilized amyloglucosidase and o-amylase and their use in the production of glucose syrups (Wilson and Lilly, 1969;Bachler et al, 1970;Park and Lima, 1973;Park, 1974;Tachauer et al, 1974;Linko et al, 1975). Others have described and compared the costs of batch and continuous process designs for the conversion of starch into dextrose and dextrose syrups by acid-enzyme and dual-enzyme processes (Sinclair, 1965;Kingma, 1966Kingma, , 1969Ewing and Harrington, 1967;Aschengreen, 1975).…”
Section: Introductionmentioning
confidence: 99%